4.1k views
0 votes
How do you solve the equation -3(4y-7)-y=-2(y-2) and check

2 Answers

2 votes

Answer:

y = 17 / 11

Step-by-step explanation:

Equation: −3(4y−7)−y=−2(y−2)

Directions: Solve for 'y' and check

Step 1: Simplify both sides of the equation

−3(4y-7)−y=−2(y−2)

(−3)(4y)+(−3)(−7)+−y=(−2)(y)+(−2)(−2) (Distribute)

−12y+21+−y=−2y+4

(−12y+−y)+(21)=−2y+4 (Combine Like Terms)

−13y+21=−2y+4

−13y+21=−2y+4

Step 2: Add 2y to both sides

−13y+21+2y=−2y+4+2y

−11y+21=4

Step 3: Subtract 21 from both sides

−11y+21−21=4−21

−11y=−17

Step 4: Divide both sides by -11

-11y/-11=-17/-11

y = 17 / 11

Check:

−3(4·17/11−7)−17/11=−2(17/11−2)

−3(4·17/11−7)−17/11 = 10/11

−2(17/11−2) = 10/11

10/11 = 10/11

User GabiMe
by
5.8k points
1 vote

In this question, you're solving for y:

Solve for y:

-3(4y - 7) - y = -2(y - 2)

use the distributive property:

-12y + 21 - y = -2y + 4

combine like terms:

-13y + 21 = -2y + 4

add 2 to both sides

-11y + 21 = 4

subtract 21 from both sides

-11y = -17

divide both sides by -11

y = 17/11

You would check your answer by plugging in 17/11 to the y variables.

User Ziaullhaq Savanur
by
5.2k points